Data from: Mollusks from the upper Shackleton Limestone (Cambrian Series 2), Central Transantarctic Mountains, East Antarctica - Claybourn, Thomas M.; Jacquet, Sarah M.; Skovsted, Christian B.; Topper, Timothy P.; Holmer, Lars E.; Brock, Glenn A. (Zenodo, 2018)
An assemblage of Cambrian Series 2, Stages 3–4 conchiferan mollusks from the Shackleton Limestone, Transantarctic Mountains, East Antarctica is formally described and illustrated. The fauna includes one bivalve, one macromollusk and ten micromollusks, including the first description of the species Xinjispira simplex outside North China. The new fauna shows some similarity to previously described micromollusks from lower Cambrian glacial erratics from the Antarctic Peninsula. The fauna, mainly composed of steinkerns, is relatively low diversity, but the presence of diagnostic taxa, including helcionelloid Mackinnonia rostrata, bivalve Pojetaia runnegari, cambroclavid Cambroclavus absonus and bradoriid Spinospitella coronata as well as the botsfordiid brachiopod Schizopholis yorkensis in the overlying Holyoake Formation correlates the succession to the Dailyatia odyssei Zone (Cambrian Stage 3–4) in South Australia. Supplementary file 1 Occurrences of species left in open nomenclature This files lists published material included in the taxa Davidonia corrugata, Xianfengella yatesi, Pelagiella subangulata and Anabarella australis. These have been included here for convenience as they are referred to in the main text, but not typically included in systematics sections for specimens with only tentative affinities for previously described species.